2018
DOI: 10.32710/tekstilvekonfeksiyon.482877
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Air Permeability of Knitted Fabric by Using Computational Method

Abstract: Air permeability is one of the very important factors which need to be considered at the development stage of textile fabrics because it affects the comfort of the clothing. During normal and extreme environmental conditions human body releases heat and the heat can be controlled by the air exchange between the body and clothing microclimate and the external environment; the exchange phenomena depends on the air permeability of the fabric. The air permeability of fabric can be evaluated by both the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Because the sample FN-7 has the lowest fabric mass per unit area among all fabric samples. This shows the inverse relationship between air permeability and fabric mass per unit area parameters [15]. Nevertheless, the air permeability of the sample FN-5 higher than the sample FN-6, although the fabric mass per unit area is the highest.…”
Section: Air Permeability and Fabric Mass Per Unit Areamentioning
confidence: 79%
“…Because the sample FN-7 has the lowest fabric mass per unit area among all fabric samples. This shows the inverse relationship between air permeability and fabric mass per unit area parameters [15]. Nevertheless, the air permeability of the sample FN-5 higher than the sample FN-6, although the fabric mass per unit area is the highest.…”
Section: Air Permeability and Fabric Mass Per Unit Areamentioning
confidence: 79%
“…For example, Liu et al used the ALE method to simulate the airdrop process of plane circular parachute, the results indicated that dynamic load decrease while the steady descent speed increase with the increase of canopy permeability. 17 The above FSI studies on permeable parachute are all based on the Ergun equation, the fabric permeability coefficients are corrected with the data of canopy fabric permeability tests, and could not be obtained by fabric structure parameters directly. Additionally, the permeability model used in above FSI research are all only applicable in incompressible flow.…”
Section: Introductionmentioning
confidence: 99%